2003
DOI: 10.1542/peds.112.4.982
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Myringitis: A Case-Control Study

Abstract: Prior studies have shown that bullous myringitis (BM) accounts for <10% of acute otitis media (AOM) cases, and that the distribution of viral and bacterial pathogens in BM is similar to that in AOM without BM, except for a relative increase in the proportion of Streptococcus pneumoniae in BM. We studied 518 cases of AOM in children aged 6 months to 12 years. Using tele-otoscopy to assist the diagnosis, we identified 41 cases (7.9%) with BM. Children who had AOM with BM were older than AOM patients without BM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…After careful cerumen removal, we systematically assessed the middle-ear status (position, translucency, color, hyperemia, light reflex, mobility of the tympanic membrane, and possible airfluid interfaces) by using pneumatic otoscopy (Macroview otoscope model 23810 [Welch Allyn]); the otoscopy score (8 grades) (OS-8) 13 ; and which ear had the worse status. Digital pneumatic video otoscopy (Jedmed, St Louis, MO) was used to document the findings.…”
Section: Tympanic-membrane Examinationmentioning
confidence: 99%
“…After careful cerumen removal, we systematically assessed the middle-ear status (position, translucency, color, hyperemia, light reflex, mobility of the tympanic membrane, and possible airfluid interfaces) by using pneumatic otoscopy (Macroview otoscope model 23810 [Welch Allyn]); the otoscopy score (8 grades) (OS-8) 13 ; and which ear had the worse status. Digital pneumatic video otoscopy (Jedmed, St Louis, MO) was used to document the findings.…”
Section: Tympanic-membrane Examinationmentioning
confidence: 99%
“…We calculated this score from our symptom questionnaire and from our systematically recorded otoscopic signs. Second, immediately after the otoscopic examination, we recorded the otoscopy score, 8 grades (OS-8 score), which McCormick et al 12 developed to measure the severity of tympanic membrane inflammation (range, 0-7). Third, we asked parents to assess their child' s overall condition (range, 0-7) at its worst within the preceding 24 hours and at study clinic, by the AOM-faces scale, which was developed by Friedman et al 13 Fourth, we used the modified AOM total severity index (AOM-Si) as suggested by McCormick et al 14 to determine the severity of AOM.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we asked parents to assess their child' s overall condition (range, 0-7) at its worst within the preceding 24 hours and at study clinic, by the AOM-faces scale, which was developed by Friedman et al 13 Fourth, we used the modified AOM total severity index (AOM-Si) as suggested by McCormick et al 14 to determine the severity of AOM. We calculated the AOM-Si score (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] by summing up the highest OS-8 score and the highest AOM-faces scale at its worst within 24 hours. Fifth, based on our symptom questionnaire, we calculated the AOM severity of symptom scale (AOM-SOS; version 3.0), which Shaikh et al 15 created.…”
Section: Methodsmentioning
confidence: 99%
“…McCormick et al [9] have created the OS-8 that focuses more on TM redness compared to the OMGRADE scale. The OS-8 also lacks the classification of a wet and contourless/ perforated TM, described as "chagrinated" in the OMGRADE scale.…”
Section: Tablementioning
confidence: 99%
“…Different scoring systems and a single AOM grading scale have previously been presented [7][8][9][10][11]. However, in our opinion, the aforementioned systems tend to overestimate the value of the parameter "redness of the TM" despite colour having been found to be of limited value in diagnosing AOM [11,12].…”
Section: Introductionmentioning
confidence: 99%